1986
DOI: 10.1002/1097-0142(19860701)58:1<18::aid-cncr2820580105>3.0.co;2-c
|View full text |Cite
|
Sign up to set email alerts
|

Cisplatin administered by the intracavitary route as treatment for malignant mesothelioma

Abstract: Twenty-one patients with malignant mesothelioma were treated with an experimental intracavitary chemotherapy regimen of weekly intraperitoneal or intrapleural cisplatin (90-100 mg/m2) with simultaneous intravenous sodium thiosulfate delivered to protect against cisplatin-induced nephrotoxicity. One of eight patients (12.5%) receiving intrapleural therapy and nine of 13 patients receiving intraperitoneal therapy demonstrated objective evidence of a clinical response, including three surgically defined major tum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
21
0
1

Year Published

1989
1989
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(24 citation statements)
references
References 6 publications
2
21
0
1
Order By: Relevance
“…11,12 Nevertheless, drugs already being used for systemic administration have been successfully administered regionally in various types of cancer. [13][14][15][16][17][18][19][20][21][22][23] The concept of local drug delivery is proposed as a method for delivering high drug concentrations to the target site while preventing exposure of vital organs to toxic drug concentrations in the systemic circulation. In this way, systemic side effects are minimized.…”
Section: Introductionsupporting
confidence: 86%
“…11,12 Nevertheless, drugs already being used for systemic administration have been successfully administered regionally in various types of cancer. [13][14][15][16][17][18][19][20][21][22][23] The concept of local drug delivery is proposed as a method for delivering high drug concentrations to the target site while preventing exposure of vital organs to toxic drug concentrations in the systemic circulation. In this way, systemic side effects are minimized.…”
Section: Introductionsupporting
confidence: 86%
“…Diversas drogas têm sido usadas com variados graus de resposta terapêutica, tais como ciclofosfamida, metrotrexato, 5-fluorouracil, cisplatina e doxorubicina [49][50][51][52][53] . A associação dos tratamentos cirúrgico, quimioterápico e radioterápico não parece trazer vantagens na sobrevida média, quando se compara cada tratamento independentemente.…”
Section: Discussão E Conclusãounclassified
“…Free cisplatin and Sustained Release Lipid Inhalation Targeting (SLIT) Cisplatin tested in vitro in a human lung tumor cell line (NCI-H460) showed that encapsulation did not alter the cytotoxic properties of the nebulized drug; IC 50 values for SLIT Cisplatin and cisplatin were found to be 0.55 F 0.05 and 0.49 F 0.04 Ag/mL, respectively. 5 Intratracheal instillation of SLIT Cisplatin versus i.v. cisplatin in Sprague-Dawley rats led to much higher ratios of lung/kidney levels for SLIT Cisplatin, indicating that it may be possible to achieve therapeutic levels with reduced exposure to kidneys, thus minimizing the potential for nephrotoxicity compared with i.v.…”
mentioning
confidence: 99%
“…In terms of localized toxicity, for beagle dogs administered a single dose of SLIT Cisplatin (2 mg/kg body weight = total deposited dose in the lungs) by inhalation and evaluated 14 days later, there were no histopathologic changes noted in the lungs, kidneys, or bone marrow. 5 SLIT Cisplatin administered by inhalation has shown significant antitumor activity in an animal model of metastatic disease (25). Briefly, in vivo antitumor activity was studied in a murine Lewis lung tumor metastasis model (C57Bl/6) where mice were i.v.…”
mentioning
confidence: 99%
See 1 more Smart Citation